Culture and conflicts in Sierra Leone mining strangers, aliens, spirits - Akiwumi, Fenda A. (Anthem Press, 2024)
In Culture and Conflicts in Sierra Leone Mining: Strangers, Aliens, Spirits, the author uses Sierra Leone as a case study to contribute to the debates on the causes and nature of mineral resource conflicts in Africa. Unlike many works that focus on the political economy and political ecology of large-scale diamond mining conflicts, this book's goal is to add to the limited literature on the persistent discord in mining areas. In so doing, the book integrates cultural conflict dimensions in analyzing the mineral commodity chain, primarily the clash between the centuries-old customary landlord-stranger land governance institution and state mining laws with colonial vestiges. It shows that these cultural conflicts challenge the effective development of the mining sector, including establishing artisanal mining as a viable complementary livelihood to farming for rural populations.